Oud neg.nr. 711234-711236. 'v. Veen, Trees Koning, Mimi Kiffen, ondernemingsraadleden, De Eendracht' - Haas, Joh. de,
Oud neg.nr. 711234-711236. 'v. Veen, Trees Koning, Mimi Kiffen, ondernemingsraadleden, De Eendracht'.